Use of Streptococcus salivarius K12 in supporting the mucosal immune function of active young subjects: A randomised double-blind study - Bertuccioli, Alexander; Gervasi, Marco; Annibalini, Giosuè; Binato, Beatrice; Perroni, Fabrizio; Rocchi, Marco B. L.; Sisti, Davide; Amatori, Stefano (Frontiers in Immunology, 2023)
Introduction: Upper respiratory tract infections (URTI) are the most common illnesses affecting athletes, causing absences from training and competition. Salivary immunoglobulin A (sIgA) is the main immune factor in saliva, and a consistent association between low concentrations of sIgA and an increased incidence of URTIs has been reported. The oral probiotic Streptococcus salivarius K12 (Blis™ K12) has been suggested to have the potential to improve oral diseases and mucosal barrier function. However, the effects of this probiotic on active young subjects performing a high-intensity training (HIT) program have not been investigated. Methods: Active young students were randomised into a treated group (S. salivarius K12) and a control (placebo) group and asked to take the product daily for 30 days. After this period, participants performed a graded exercise test and five HIT sessions, all within 3 days. They were also asked to complete the Wisconsin Upper Respiratory Symptom Survey daily to monitor URTI's presence. Before and after the 30 days, and at 0h, 24h and 72h after the last training session, saliva samples were collected to quantify sIgA level, secretion rate, and flow. The effect of S. salivarius K12 intake on these parameters was tested using an ANOVA for repeated measures. Results: Twenty (M=16, F=4) young subjects (23.5 ± 2.3 years old) participated in the study. The total accumulated training load (sRPE) in the supplementation period was similar in the two groups (treated: 4345 ± 3441 AU; control: 4969 ± 4165 AU; p > 0.05). Considering both sIgA level and secretion rate, significant time (F(4,15) = 3.38; p = 0.037; F(4,15) = 6.00; p = 0.004) and time×group interactions (F(4,15) = 2.49; p = 0.049; F(4,15) = 5.01; p = 0.009) were reported, with the treated group showing higher sIgA levels at 72h post-exercise and increased secretion rate both at 0h and 72h. The number of URTI episodes was similar in the treated and control groups (χ² = 1.83; p > 0.05). Conclusion: This study demonstrates that relatively short-term S. salivarius K12 supplementation increased sIgA level and secretion in healthy subjects performing a demanding exercise-training programme composed of HIT sessions.